2007
DOI: 10.1007/s10551-007-9430-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Commitment to Moral Self-improvement and Religiosity on Ethics of Business Students

Abstract: Using survey methodology we examined the relationships between commitment to moral selfimprovement (CMSI), religiosity, ethical problem recognition, and behavioral intentions in a sample of 242 business students. Results of the study suggest that CMSI predicts ethical problem recognition and behavioral intentions. Our findings also suggest that CMSI is positively related to religiosity. The study provides some evidence of CMSI being a mediator in the influence of religiosity on ethical problem recognition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 44 publications
5
61
1
3
Order By: Relevance
“…The results of this study do not support a finding Budiman [46] that religiosity moderating the intention of buying a pirated bag, as well as the findings Vitell and Paolillo [47], and Kurpis et al [48][49][50][51][52][53][54][55] which indicated person religiosity can push a positive effect on ethical behavior. Religiosity that exists in students at private colleges Islamic religious background is not capable reinforce the students to do voluntary WOM marketing communications.…”
Section: Resultscontrasting
confidence: 99%
“…The results of this study do not support a finding Budiman [46] that religiosity moderating the intention of buying a pirated bag, as well as the findings Vitell and Paolillo [47], and Kurpis et al [48][49][50][51][52][53][54][55] which indicated person religiosity can push a positive effect on ethical behavior. Religiosity that exists in students at private colleges Islamic religious background is not capable reinforce the students to do voluntary WOM marketing communications.…”
Section: Resultscontrasting
confidence: 99%
“…Singhapakdi et al (1996) mengembangkan intrumen yang handal dan valid untuk mengukur bagaimana para pemasar (marketer) mempersepsikan peran etika dan tanggung jawab sosial dalam sebuah organisasi yang efektif. Kurpis et al (2008) mencatat bahwa karena sifat khusus dari bisnis, profesional bisnis cenderung menghadapi dilema etika yang unik untuk profesi mereka. Demikian juga dengan profesi konsultan pajak.…”
Section: Konsultan Pajakunclassified
“…In addition to these findings, there are studies which had not found any significant relationship between moral sensitivity and ethical behavior intention. Due to these inconsistencies, many research studies had suggested that to understand this phenomenon, new studies should include a number of variables such as personality, religiosity, social interactions, life events, and opportunity to engage in moral actions which may influence the formation of commitment to moral judgments (for example, Hart, 2005;Kurpis, Beqiri, & Helgeson, 2008).…”
Section: Moral Norms and Personal Traitsmentioning
confidence: 99%